Shotgun Label-Free Proteomic Analyses of the Oyster Parasite Perkinsus Marinus - Márcia P. Leibowitz; Guilherme C. Tavares; Felipe L. Pereira; Cristiana Perdigão; Vasco Azevedo; Henrique C. P. Figueiredo (Journal of Proteomics and Genomics Research, 2017)
Perkinsus marinus is an intracellular parasitic protozoan that is responsible for serious disease epizootics in marine bivalve mollusks worldwide. Despite all available information on P. marinus genomics, more baseline data is required at the proteomic level. Our aim was to study the proteome profile of in vitro cultured P. marinus isolated from oysters Crassostrea spp. using a label-free shotgun UDMSE approach. A total of 4073 non-redundant proteins were identified across three biological replicates with stringent identification. Proteins specifically related to adaptive survival, cell recognition, antioxidants, regulation of apoptosis and others were detected. Important virulence factors of P. marinus were identified including serine protease and iron-dependent superoxide dismutase. Other proteins with involvement in several pathogens invasion strategies were rhoptries, serine-threonine kinases, and protein phosphatases. Interestingly, peptides corresponding to retroviruses polyproteins were identified in all replicates. The interactomic analysis of P. marinus proteins demonstrated extensive clusters network related to biological processes. In conclusion, we provide the first comprehensive proteomic profile of P. marinus that can be useful for further investigations on Perkinsus biology and virulence mechanisms.
Keywords: Crassostrea rhizophorae